Factors affecting public acceptance of large-scale residential development projects in the environmental impact assessment process: 10.55131/jphd/2026/240203 - Sasina Butnakhon; Puek Tantriratna; Uraiwan Inmuong; Kavin Thinkhamrop (Journal of Public Health and Development, 2026)
Large-scale residential development projects (LRDPs) in Thailand require an environmental impact assessment, which includes public participation and hearings to inform stakeholders, gather feedback, and develop appropriate mitigation measures to enhance project acceptance. This study examined the factors affecting public acceptance of large-scale residential development projects in urban communities. A cross-sectional study was conducted from September to December 2024 with 1,161 residents living within a 1-kilometer radius of three proposed development sites in urban communities in Khon Kaen, Chonburi, and Bangkok provinces. Data were collected using a validated questionnaire and analyzed with a generalized linear mixed model to determine adjusted odds ratios (AORs) and 95% confidence intervals (CIs). The overall acceptance rate was 80.45%. Key factors associated with acceptance included being younger than 30 years (AOR = 1.91; 95% CI: 1.24–2.95), working in retail or merchant businesses (AOR = 2.58; 95% CI: 1.11–6.00), living in rental or welfare housing (AOR = 1.88; 95% CI: 1.30–2.71), using property solely for commercial purposes (AOR = 2.08; 95% CI: 1.15–3.76), residing over 500 meters from the site (AOR = 9.68; 95% CI: 3.38–27.78), having high information perception (AOR = 4.71; 95% CI: 1.51–14.67), and holding positive attitudes toward project impacts (AOR = 8.26; 95% CI: 5.47–12.48). The findings emphasize the need for targeted community engagement, transparent communication, participatory planning, and effective environmental mitigation strategies to enhance public acceptance of LRDPs.